High thermal conductive nonlinear conductance composite material containing vertical nanowire array and preparation method and application thereof

CN122465313BActive Publication Date: 2026-10-30SHENZHEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610787313.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-03
Publication Date
2026-10-30
Estimated Expiration
2046-06-03

AI Technical Summary

Technical Problem

但现有掺杂改性技术仍存在难以克服的技术瓶颈与固有缺陷:若功能填料填充比例较低,复合材料导热性能提升幅度有限,无法及时消散电场畸变区域因泄漏电流集聚产生的局部热累积,难以抑制绝缘热击穿风险,同时材料非线性伏安响应强度不足,无法对局部强电场形成有效抑制与自适应均化,难以从根源上缓解电场集中引发的绝缘老化问题;若盲目提高填料填充用量,虽可一定程度提升电热性能,但会显著劣化复合材料的力学强度、韧性及注塑浇注等成型加工性能,还易出现填料团聚、界面缺陷增多的问题,同时大幅增加原材料成本与制备能耗,经济性与工程适用性较差

Benefits of technology

本发明通过磁性改性耦合磁场定向的协同设计,在极低填料填充条件下,同步优化复合材料导热性能与非线性电导特性,有效解决现有绝缘材料散热差、电场调控能力弱以及常规改性材料填料掺量大、加工性差等技术痛点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122465313B_ABST
    Figure CN122465313B_ABST
Patent Text Reader

Abstract

The application discloses a high-thermal-conductivity nonlinear conductance composite material containing a vertical nanowire array and a preparation method and application thereof, and relates to the technical field of nanocomposite insulating materials.The modified semiconductor nanowire with Fe3O4 nanoparticles loaded on the surface is adopted, and a vertical directional longitudinal arrangement structure of the modified nanowire is formed in a polymer matrix by relying on a magnetic field assisted curing process.The efficient heat conduction and charge transport network can be constructed in the range of 1% to 5% volume fraction by adjusting the Fe3O4 loading amount and the low filling amount of the modified nanowire.Compared with a traditional magnetic field orientation scheme, the amount of fillers is significantly reduced, the matrix processing performance is improved, and the preparation cost is reduced.The material has excellent insulation performance, can self-adaptively adjust the conductivity to balance the local electric field under an abnormal electric field, and has good heat dissipation capacity, and the adjustable range of parameters is wide, so that the material can be adapted to the insulation, voltage equalization and overvoltage protection scenes of high-voltage electrical equipment of different voltage grades.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanocomposite insulating materials technology, and in particular to a high thermal conductivity and nonlinear conductivity composite material containing a vertical nanowire array, its preparation method, and its application. Background Technology

[0002] With the rapid iterative development of ultra-high voltage direct current (UHVDC) transmission and smart grid technologies, high-voltage and extra-high voltage electrical equipment is gradually evolving towards miniaturization, high power density, and long service life. The electrical insulation reliability, heat dissipation capacity, and adaptive electric field control performance of the internal insulation systems have become core factors in ensuring the safe and stable operation of power equipment. Epoxy resin, silicone rubber, and other polymeric materials, due to their excellent electrical insulation, processability, and mechanical stability, are widely used in core insulation components for power transmission and transformation, such as insulators, wall bushings, cable accessories, and transformer insulation components. However, polymer matrices generally have inherent shortcomings such as low thermal conductivity and limited dielectric properties. Under long-term energized operation, the equipment is prone to local electric field distortion and electric field concentration due to multiple factors such as material dielectric parameter mismatch, abrupt structural changes, and defects at the matrix-filler interface. At the same time, leakage current accumulation in strong field areas can easily cause local heat accumulation, and the heat is difficult to dissipate quickly. Under long-term electrothermal coupling, the insulating medium will age and its performance will degrade. In severe cases, it can induce partial discharge, insulation thermal breakdown, or even failure and shutdown of the entire equipment, which greatly threatens the safe operation of high-voltage power systems.

[0003] To address the issues of uneven electric field distribution and insufficient heat dissipation in polymer insulation materials, existing technologies generally employ modification schemes involving the doping of semiconductor inorganic fillers into the polymer matrix. By introducing functional fillers, the composite material is endowed with certain nonlinear electrical conductivity and thermal conductivity, aiming to achieve passive electric field homogenization and localized heat dissipation. However, existing doping modification technologies still face insurmountable technical bottlenecks and inherent defects: if the proportion of functional fillers is low, the improvement in the thermal conductivity of the composite material is limited, failing to promptly dissipate localized heat accumulation caused by leakage current in areas of electric field distortion, making it difficult to suppress the risk of insulation thermal breakdown. Simultaneously, the material's nonlinear volt-ampere response is insufficient, failing to effectively suppress and adaptively homogenize localized strong electric fields, making it difficult to fundamentally alleviate the insulation aging problem caused by electric field concentration. Blindly increasing the filler content, while improving electrothermal performance to some extent, significantly degrades the mechanical strength, toughness, and molding / processing properties of the composite material, and easily leads to filler agglomeration and increased interface defects. Furthermore, it significantly increases raw material costs and manufacturing energy consumption, resulting in poor economic efficiency and engineering applicability. More importantly, in existing modified systems, functional fillers are mostly randomly and disorderedly dispersed in the polymer matrix, making it impossible to construct continuous and orderly conductive and thermally conductive pathways. This makes it difficult to achieve precise synergistic control of nonlinear electrical properties and directional thermal conductivity, and the technical challenge of simultaneously optimizing electrothermal performance under low filler doping conditions has not yet been effectively overcome.

[0004] Meanwhile, conventional random blending of fillers lacks methods for orderly control of the microstructure, making it impossible to regulate key electrical parameters such as the trap energy level, threshold field strength, and nonlinear coefficient of composite materials. Although existing technologies include magnetic field-induced particle orientation and one-dimensional nanofiller modification, they have not yet achieved a balance between excellent nonlinear current-voltage characteristics, high directional thermal conductivity, good mechanical processing properties, and engineering economy of composite materials with low filler doping levels. This fails to meet the stringent requirements of current UHV electrical equipment for intelligent insulation materials that provide reliable insulation under low fields, adaptive voltage equalization under high fields, efficient directional heat dissipation, and long lifespan and aging resistance.

[0005] Therefore, developing a magnetic field-oriented nanocomposite smart insulating material with a reasonable structural design, controllable preparation process, and low filler content that can achieve synergistic improvement in electrothermal performance is of great engineering application value and practical significance in overcoming the inherent contradictions and performance bottlenecks of existing insulation modification technologies. Summary of the Invention

[0006] The purpose of this invention is to provide a high thermal conductivity and nonlinear electrical conductivity composite material containing a vertical nanowire array, its preparation method, and its application, so as to solve the problems existing in the prior art.

[0007] To achieve the above objectives, the present invention provides the following solution: This invention provides a high thermal conductivity and nonlinear electrical conductivity composite material containing a vertical nanowire array, comprising a polymer matrix and modified semiconductor nanowires dispersed within the polymer matrix; the modified semiconductor nanowires are semiconductor nanowires with Fe3O4 nanoparticles loaded on their surface; the modified semiconductor nanowires are arranged in a vertically oriented structure within the polymer matrix with magnetic field assistance. The Fe3O4 nanoparticles account for 1 to 4% of the mass of the modified semiconductor nanowires by mass fraction. The modified semiconductor nanowires comprise 1% to 5% of the polymer matrix by volume fraction. Further, the polymer matrix includes at least one selected from epoxy resin, polyimide, polyethylene terephthalate, polydimethylsiloxane, polyurethane, polyvinylidene fluoride, acrylonitrile-butadiene-styrene copolymer, polyvinyl chloride, polyethylene, polystyrene, polypropylene, polymethyl methacrylate, polyamide, polyoxymethylene, polycarbonate, styrene-butadiene rubber, silicone rubber, cis-butadiene rubber, isoprene rubber, chloroprene rubber, and natural rubber.

[0008] Furthermore, the epoxy resin comprises a resin substrate, a curing agent, and a latent agent; The resin substrate is any one of bisphenol A type epoxy resin, bisphenol F type epoxy resin, polyphenol type glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, and alicyclic epoxy resin. The curing agent is either methylhexahydrophthalic anhydride or methyltetrahydrophthalic anhydride; The luring agent is any one of neodymium acetylacetonate, 2-methylimidazole, and 2-ethyl-4-methylimidazole.

[0009] Furthermore, the weight ratio of the resin substrate, curing agent, and latent agent is 100:(90-120):(0.5-1); the mixture is carried out at a stirring temperature of 40-80°C and a stirring time of 1 hour.

[0010] Furthermore, the semiconductor nanowires include SiC nanowires.

[0011] The present invention also provides a method for preparing the above-mentioned high thermal conductivity and nonlinear conductivity composite material containing a vertical nanowire array, comprising the following steps: The modified semiconductor nanowires are mixed with the polymer matrix raw material and then cured in a magnetic field environment to obtain the high thermal conductivity and nonlinear electrical conductivity composite material containing a vertical nanowire array.

[0012] Furthermore, the curing process employs a gradient curing technique, specifically: maintaining a temperature of 80-100℃ for 1-2 hours, maintaining a temperature of 100-115℃ for 1-2 hours, and maintaining a temperature of 135℃-150℃ for 1-2 hours.

[0013] Furthermore, the method for preparing the modified semiconductor nanowires includes the following steps: Fe3O4 nanoparticles were loaded onto the surface of the semiconductor nanowires by electrostatic adsorption, and the modified semiconductor nanowires were obtained by separation and drying.

[0014] Furthermore, the magnetic field environment is achieved by using two objects spaced 3.5 cm apart, each with a size of 50 mm. 50 It is made of 10mm magnets and has a central magnetic field strength of 300Gs.

[0015] The present invention also provides the application of the above-mentioned high thermal conductivity and nonlinear conductivity composite material containing vertical nanowire arrays as an insulating component, electric field equalization component or overvoltage suppression component of high voltage electrical equipment.

[0016] This invention innovatively employs a coupled preparation approach combining magnetic particle modification and parameter-controllable magnetic field orientation. Utilizing the dual quantitative variables of filler loading ratio and filler dosage, only a low amount of modified nanofiller is needed to synergistically regulate the microstructure and macroscopic properties of the composite material, ultimately producing a high thermal conductivity and nonlinear electrical conductivity composite material containing a vertical nanowire array. This invention is not a simple superposition of two processes; relying on the synergistic effect of oriented interconnected networks and traps, it overcomes the technical bottleneck of high filler dependence in traditional materials. By linking a microscopic thermally conductive network and charge transport mechanism with extremely low filler dosage, it breaks the dependence of traditional composite materials on high filler content. With a small amount of modified filler, it simultaneously optimizes thermal conductivity and electric field adaptability, specifically addressing the poor heat dissipation performance and lack of adaptive electric field control function of traditional insulating materials, as well as the numerous technical drawbacks of conventional magnetic field-oriented composite materials, such as large filler dosage, single performance, non-adjustable parameters, large filler dosage, and limited applicability.

[0017] From a microscopic perspective, the quantitative control of material loading is the core key to achieving differentiated performance and distinguishing this invention from conventional oriented materials. This invention loads Fe3O4 magnetic nanoparticles onto the surface of semiconductor nanowires at a predetermined mass ratio. The material loading directly determines the magnetic response intensity and charge trap density of the nanowires, serving as a crucial prerequisite for subsequent material forming and performance control. On one hand, adjusting the Fe3O4 loading ratio according to actual working conditions precisely alters the magnetic sensitivity of the modified nanowires, enabling them to achieve oriented arrangement under a uniform external magnetic field. A small amount of modified nanowires can construct a continuous and orderly longitudinal transport network within the matrix, fundamentally avoiding the problems of filler agglomeration and disordered orientation under high-filling conditions. In contrast, conventional magnetic field orientation techniques directly use unmodified nanowires, which lack magnetic response characteristics and cannot achieve high-precision, controllable orientation. On the other hand, Fe3O4 nanoparticles with different loadings can construct charge trap structures of varying numbers and depths at the filler-matrix interface. Without the need for high-dosage filler enrichment and stacking, the modified nanowires, uniformly dispersed under low-filling conditions, can impart stable and tunable nonlinear conductivity to the material through multi-level interfacial trapping effects, completely differentiating it from the single-function mode of pure nanowires relying solely on their own bulk conductivity. During the magnetic field-assisted curing stage, the modified nanowires, combined with their volume fraction, construct continuous longitudinal network channels of varying sizes within the polymer matrix. The filler loading and particle loading work together to not only build efficient thermal conduction pathways as needed, reduce interfacial thermal resistance, and improve the overall heat dissipation capacity of the material, but also, in conjunction with the charge trap structures, achieve controllable regulation of charge capture and release behavior.

[0018] At the level of intelligent response performance, dual quantitative parameters jointly determine the material's adaptive electric field adjustment capability, achieving a dynamic and controllable balance between insulation performance, thermal conductivity, and nonlinear conductivity under low filler content. When the modified nanowire filling amount and Fe3O4 loading amount are within the range defined by this invention, the composite material can be adapted to the normal operating conditions of high-voltage electrical equipment: under normal operating electric field, the internal transmission path is in a disconnected state, and the material maintains high insulation properties to meet basic insulation requirements; when the equipment experiences abnormal conditions such as local electric field distortion or transient overvoltage, the high electric field will excite the charge in the interface trap to undergo energy level transitions, and the transmission network can be quickly connected by a small amount of oriented modified nanowires, without the need for high filler content to support charge conduction. Among them, the Fe3O4 loading amount determines the charge trap threshold, and the nanowire filling amount affects the charge transmission efficiency. The two together regulate the material's threshold field strength and nonlinear coefficient, causing the material's conductivity to increase adaptively, autonomously dissipate excess charge, and uniformize the local electric field, avoiding the insulation structure from being broken down and damaged. This integrated intelligent characteristic of sensing and response, achieved through dual-variable regulation, is a core innovation that cannot be replicated by any conventional magnetic field orientation process.

[0019] In existing technologies, conventional magnetic field orientation is merely a simple physical arrangement method without quantitative control logic. It can only slightly optimize the single thermal or electrical conductivity of materials, with a fixed performance upper limit, making it unsuitable for diverse operating conditions. Furthermore, insulation performance, thermal conductivity, and nonlinear conductivity are inherently interdependent, and conventional modification schemes struggle to achieve a balance among all three. High thermal conductivity often sacrifices insulation performance, while nonlinear characteristics are extremely sensitive to interface trap density. This invention relies on two controllable variables—the mass fraction of Fe3O4 loading and the volume fraction of modified nanowires—to form a multi-dimensional performance control system. Combined with the vertical micro-network constructed by magnetic field orientation, it simultaneously achieves multiple functions—high thermal conductivity, adjustable nonlinear conductivity, and high insulation stability—within an extremely low addition range, breaking through the technical bottleneck of conventional oriented materials' fixed performance and single function. Operators can match optimal material parameters to customize insulating components with corresponding threshold field strength and thermal conductivity according to the usage requirements of equipment at different voltage levels, thus broadening the adaptability range. Meanwhile, the modified nanowires are tightly bonded to the polymer matrix interface, and the oriented network structure has strong structural stability under complex service environments of temperature change and alternating electric field. It is not prone to misalignment or collapse and can stably perform thermal conductivity and electric field regulation functions for a long time. Its engineering application value is far higher than that of conventional magnetic field oriented composite materials.

[0020] The present invention discloses the following technical effects: This invention utilizes a synergistic design of magnetic modification coupled with magnetic field orientation to simultaneously optimize the thermal conductivity and nonlinear electrical conductivity of composite materials under extremely low filler conditions. This effectively addresses the technical pain points of existing insulating materials, such as poor heat dissipation and weak electric field control capabilities, as well as the large filler content and poor processability of conventional modified materials.

[0021] This invention enables the construction of a continuous and stable longitudinal thermal conductivity and charge transport network within a low filler volume fraction range. Compared to disordered filling and conventional magnetic field-oriented systems, it significantly reduces the filler addition threshold and avoids problems such as filler agglomeration, matrix performance degradation, and increased manufacturing costs caused by high filler content. The well-oriented microstructure effectively reduces interfacial contact thermal resistance, significantly improves the overall thermal conductivity of the composite material, and can promptly dissipate the accumulated heat generated during equipment operation, alleviate the thermal aging problem of insulation materials, and extend the service life of components.

[0022] Meanwhile, the controllable distribution of Fe3O4 particles on the surface of the modified nanowires can introduce multi-level charge traps, combined with directional short-range transport channels, giving the material excellent and tunable electric field adaptive characteristics. Under normal conditions, the material maintains high insulation properties, meeting the basic insulation requirements of electrical equipment; under abnormal operating conditions such as overvoltage and electric field distortion, it can autonomously discharge charges and unify the local electric field. Furthermore, operators can flexibly adjust the threshold field strength and nonlinear coefficient by controlling the Fe3O4 loading and filler doping amount, adapting it to high-voltage insulation scenarios of different voltage levels, making its overall cost-effectiveness and engineering practicality even more outstanding. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 Characterization of the SiC@1%Fe3O4 composite nanowires prepared in Example 1 of this invention; wherein, a is TEM image and EDSMapping energy spectrum, b is XRD image, c is XPS image, and d is Fe 2p fine spectrum analysis.

[0025] Figure 2 In the figure, a is the current-voltage characteristic curve of SiC@Fe3O4 composite nanowires with different Fe3O4 loadings, b is the current-voltage characteristic curve of randomly filled composite material with the same Fe3O4 loading but different nanowire filling amounts, and c is the current-voltage characteristic curve of magnetically oriented composite material with the same Fe3O4 loading but different nanowire filling amounts.

[0026] Figure 3 Scanning electron microscopy (SEM) images of the epoxy resin composites prepared in Examples 5(a) and 13(b).

[0027] Figure 4 Comparison of Weibull distribution of breakdown field strength for composite materials with different volume fractions; where a is the breakdown Weibull distribution curve of randomly filled composite material without magnetic field, and b is the breakdown Weibull distribution curve of magnetically assisted vertically oriented composite material. Detailed Implementation

[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0029] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0030] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0031] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0032] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0033] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.

[0034] Example 1: Preparation of SiC@1%Fe3O4 composite nanowires (1) Weigh 4g of silicon carbide nanowires, add 200mL of deionized water, ultrasonically disperse for 1h, and magnetically stir at room temperature to obtain a uniform silicon carbide nanowire dispersion. (2) Measure 190 μL of EMG-605 magnetic fluid (each 10 mL of EMG-605 contains 2.1 g of Fe3O4 nanoparticles), add 8 mL of deionized water to dilute and stir evenly to prepare a magnetic fluid dilution solution.

[0035] (3) Place the silicon carbide nanowire dispersion in a room temperature magnetic stirring state, and slowly add the magnetic fluid diluent drop by drop. After the addition is completed, let it stand for 0.5 h. Fe3O4 nanoparticles are uniformly loaded on the surface of silicon carbide nanowires by electrostatic adsorption.

[0036] (4) The mixture system of step (3) is filtered and separated, the solid product is collected, and the obtained solid powder is placed in a constant temperature drying oven and dried at 80°C for 12 hours. Finally, SiC@1%Fe3O4 composite nanowire powder with a Fe3O4 loading mass fraction of 1% is obtained.

[0037] Example 2: Preparation of SiC@2%Fe3O4 composite nanowires The only difference from Example 1 is that the amount of EMG-605 added is 380 μL.

[0038] Example 3: Preparation of SiC@3%Fe3O4 composite nanowires The only difference from Example 1 is that the amount of EMG-605 added is 570 μL.

[0039] Example 4: Preparation of SiC@4%Fe3O4 composite nanowires The only difference from Example 1 is that the amount of EMG-605 added is 760 μL.

[0040] To characterize the microstructure, elemental composition, crystal structure, and valence state of the prepared modified nanowires, the SiC@1%Fe3O4 composite nanowires (labeled as SiC@Fe3O4) prepared in Example 1 were subjected to transmission electron microscopy (TEM), elemental distribution analysis, X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) analyses. The relevant characterization results are as follows: Figure 1 As shown. Figure 1 In the diagram, a represents the TEM image and EDS mapping energy spectrum, b represents the XRD pattern, c represents the XPS pattern, and d represents the fine spectral analysis of Fe 2p.

[0041] from Figure 1 Figure a shows that the nanowires have a uniform diameter of approximately 400 nm. The elemental mapping reveals that the nanowires contain a large distribution of Si, C, Fe, and O elements.

[0042] To further characterize the crystal and molecular structure of the nanofibers, X-ray diffraction was used to observe the crystal structure of the nanofibers, such as... Figure 1 As shown in b, the strong diffraction peaks at 33.8°, 35.7°, 41.5°, 60.6°, 71.9°, and 75.5° correspond to the (101), (102), (104), (110), (116), and (0012) crystal planes of SiC, respectively (refer to XRD standard card PDF#29-1131). The diffraction peaks of Fe3O4 are weaker, with peaks at 30.6°, 43.5°, 57.5°, and 63° corresponding to the (220), (400), (511), and (440) crystal planes of Fe3O4, respectively (refer to XRD standard card PDF#19-0629). The (311) crystal plane at 35.5° coincides with the (102) crystal plane of SiC due to its proximity. This may be due to the lower loading and smaller particle size of Fe3O4.

[0043] XPS was used to further characterize the elemental composition of the nanowires and the valence state of Fe, such as Figure 1 c and Figure 1As shown in d, the full spectrum reveals spectral peaks for each orbital of the four elements Si, C, O, and Fe, consistent with XRD results indicating the presence of two compounds: SiC and Fe3O4. Comparing the full spectra of SiC and SiC@Fe3O4, characteristic peaks for Fe 3p and Fe 2p are observed at 56.3 eV and 711 eV, respectively, further confirming the successful loading of Fe3O4 nanoparticles. The Fe2p characteristic peak consists of two main peaks, at 710.1 eV and 723.4 eV, corresponding to Fe 2p... 3 / 2 With Fe 2p 1 / 2 Two characteristic peaks, each containing Fe. 3+ with Fe 2+ The contribution corresponds to the simultaneous presence of Fe in Fe3O4. 3+ with Fe 2+ The valence states of the two Fe elements.

[0044] To investigate the influence of different Fe3O4 loading on the electrical properties of modified nanowires, the radial current-voltage characteristics of the SiC@Fe3O4 composite nanowires prepared in Examples 1-4 were tested. The test results are shown in Table 1. The test results show that the overall trend of the current-voltage characteristics of the composite nanowires prepared in each example is similar; as the mass fraction of Fe3O4 loading on the SiC nanowire surface gradually increases, the varistor voltage of the nanowire shows a significant increase.

[0045] Table 1 The nanomaterials prepared above were used to prepare epoxy resin composites. The epoxy resin composites were specifically named x%SiC@y%Fe3O4ORI, where SiC represents silicon carbide, Fe3O4 represents iron(II,III) oxide, x represents the volume fraction of nanowires, y represents the mass fraction of iron(II,III) oxide in the total mass of nanowires, ORI indicates magnetically assisted oriented composite material, and no ORI indicates randomly filled composite material. In the specific preparation process, the specific values ​​of x and y were directly quantified by the mass of nanowires and the volume of EMG-605 during synthesis.

[0046] Example 5: Preparation of 5%SiC@2%Fe3O4ORI composite material (1) 30.66 parts by weight of the SiC@2%Fe3O4 nanowires prepared in Example 2 were added to sufficient N,N-dimethylformamide and ultrasonically dispersed for 30 min to obtain a uniform nanowire dispersion. (2) Add 100 parts by weight of bisphenol A epoxy resin to the dispersion obtained in step (1) and stir at 120°C for 4-5 h until N,N-dimethylformamide is completely volatilized; (3) Add 110 parts by weight of methylhexahydrophthalic anhydride and 0.5 parts by weight of 2-ethyl-4-methylimidazolium to the system in step (2) and stir for 30 min; then transfer the mixture into a high-temperature vacuum drying oven, set the temperature to 70℃, and vacuum for 0.5 h until the bubbles in the material disappear. (4) The degassed mixture is injected into a polytetrafluoroethylene mold and the mold is placed in a uniform magnetic field formed by two high-temperature magnets for gradient curing: first, it is cured at 100°C for 1 hour, then the temperature is raised to 115°C for 1 hour, and finally the temperature is raised to 135°C for 1 hour to obtain 5% SiC@2% Fe3O4ORI composite material.

[0047] Example 6 Preparation of 5%SiC@1%Fe3O4ORI composite material The only difference from Example 5 is that the SiC@1% Fe3O4 composite nanowires prepared in Example 1 were used as the raw material, while the other operation steps and process parameters remained the same.

[0048] Example 7 Preparation of 5%SiC@3%Fe3O4ORI composite material The only difference from Example 5 is that the SiC@3% Fe3O4 composite nanowires prepared in Example 3 were used as the raw material, while the other operation steps and process parameters remained the same.

[0049] Example 8 Preparation of 5%SiC@4%Fe3O4ORI composite material The only difference from Example 5 is that the SiC@4% Fe3O4 composite nanowires prepared in Example 4 were used as the raw material, while the other operation steps and process parameters remained the same.

[0050] Example 9 Preparation of 1% SiC@2% Fe3O4ORI composite material The only difference from Example 5 is that the volume fraction of SiC@2% Fe3O4 composite nanowires in the composite material is controlled to be 1%, while the other operation steps and process parameters remain the same.

[0051] Example 10: Preparation of 2% SiC@2% Fe3O4ORI composite material The only difference from Example 5 is that the volume fraction of SiC@2%Fe3O4 composite nanowires in the composite material is controlled at 2%, while the other operation steps and process parameters remain the same.

[0052] Example 11 Preparation of 3% SiC@2% Fe3O4ORI composite material The only difference from Example 5 is that the volume fraction of SiC@2%Fe3O4 composite nanowires in the composite material is controlled to be 3%, while the other operation steps and process parameters remain the same.

[0053] Example 12 Preparation of 4% SiC@2% Fe3O4ORI composite material The only difference from Example 5 is that the volume fraction of SiC@2%Fe3O4 composite nanowires in the composite material is controlled at 4%, while the other operation steps and process parameters remain the same.

[0054] Example 13 Preparation of 5% SiC@2% Fe3O4 composite material The only difference from Example 5 is that no magnetic field is applied during the curing process; all other operating steps and process parameters remain the same.

[0055] Example 14 Preparation of 5% SiC@4% Fe3O4 composite material The only difference from Example 5 is that no magnetic field is applied during the curing process; the raw material used is the SiC@4% Fe3O4 composite nanowire prepared in Example 4, and the other operation steps and process parameters are kept the same.

[0056] Example 15 Preparation of 1% SiC@4% Fe3O4ORI composite material The only difference from Example 5 is that the volume fraction of the composite nanowires in the composite material is controlled at 1%, and the raw material is the SiC@4% Fe3O4 composite nanowires prepared in Example 4. All other operation steps and process parameters remain the same.

[0057] Example 16 Preparation of 2% SiC@4% Fe3O4ORI composite material The only difference from Example 5 is that the volume fraction of the composite nanowires in the composite material is controlled at 2%, and the raw material is the SiC@4% Fe3O4 composite nanowires prepared in Example 4. All other operation steps and process parameters remain the same.

[0058] Example 17 Preparation of 3% SiC@4% Fe3O4ORI composite material The only difference from Example 5 is that the volume fraction of the composite nanowires in the composite material is controlled at 3%, and the raw material is the SiC@4% Fe3O4 composite nanowires prepared in Example 4. All other operation steps and process parameters remain the same.

[0059] Example 18 Preparation of 4% SiC@4% Fe3O4ORI composite material The only difference from Example 5 is that the volume fraction of the composite nanowires in the composite material is controlled at 4%, and the raw material is the SiC@4% Fe3O4 composite nanowires prepared in Example 4. All other operation steps and process parameters remain the same.

[0060] Example 19 Preparation of 1% SiC@4% Fe3O4 composite material The only difference from Example 15 is that no magnetic field is applied during the curing process.

[0061] Example 20 Preparation of 2% SiC@4% Fe3O4 composite material The only difference from Example 16 is that no magnetic field is applied during the curing process.

[0062] Example 21 Preparation of 3% SiC@4% Fe3O4 composite material The only difference from Example 17 is that no magnetic field is applied during the curing process.

[0063] Example 22 Preparation of 4% SiC@4% Fe3O4 composite material The only difference from Example 18 is that no magnetic field is applied during the curing process.

[0064] Example 23 Preparation of 5% SiC Composite Material The only difference from Example 5 is that untreated SiC nanowires were used as raw materials, no magnetic field was applied during the curing process, and all other operation steps and process parameters remained the same.

[0065] The epoxy resin composite materials prepared in Examples 5 and 13 were subjected to scanning electron microscopy (SEM) tests to observe the microstructure of the materials. The test results are as follows: Figure 3 As shown in Table 2. Simultaneously, the electrical properties of the epoxy resin composite materials from Examples 5-14 were tested, and the nonlinear coefficient and threshold field strength of the samples were measured.

[0066] Table 2 This invention uses scanning electron microscopy (SEM) to observe the cross-sectional morphology of the epoxy resin composite materials obtained in Examples 5 and 13. During sample preparation, the samples were first rapidly frozen with liquid nitrogen to induce brittle fracture, ensuring the integrity of the cross-sectional structure. Then, the fracture surface was sputter-coated with gold to improve the observation effect. The microscopic morphology results are shown in Figure 3. As can be seen from the figure, in the randomly filled system, the nanowires are randomly distributed within the cross-section; while in the composite material treated with magnetic field orientation, the nanowires are regularly arranged longitudinally, making it easier to form continuous longitudinal conductive pathways. Simultaneously, it was observed that the nanowires are tightly bonded to the epoxy resin matrix, with no obvious defects at the interface.

[0067] Under the condition that the filler volume fraction is 5 vol%, the nonlinear coefficient of the magnetically oriented composite material is significantly higher than that of the randomly filled sample. For example... Figure 2 Figure a shows the current-voltage (V / V) characteristics of SiC@Fe3O4 composite nanowires with different Fe3O4 loadings; figure b shows the V / V characteristics of randomly filled composite materials with the same Fe3O4 loading but different nanowire filling amounts; and figure c shows the V / V characteristics of magnetically oriented composite materials with the same Fe3O4 loading but different nanowire filling amounts. The reason for this is that oriented SiC nanowires can construct more charge conduction paths, facilitating charge release and thus resulting in a higher nonlinear coefficient. Simultaneously, the conductive pathways formed by the oriented nanowires are shorter, requiring only a lower electric field to construct a complete charge transport channel, thus their threshold field strength is lower than that of the randomly filled samples.

[0068] At the same filling amount of 5 vol%, all samples exhibited excellent nonlinear conductivity. With increasing Fe3O4 loading on the nanowire surface, the threshold electric field of the composite material gradually increased. This phenomenon is attributed to the increased number of grain boundaries and deeper charge trap energy levels resulting from the introduction of Fe3O4 particles, requiring a higher electric field for the samples to exhibit nonlinear conductivity.

[0069] The thermal conductivity of Examples 8 and 14-22 was tested, and the results are shown in Table 3. The thermal conductivity was measured using a NETZSCH LFA 500 laser scattering thermal conductivity meter (Germany) to determine the vertical thermal conductivity of the composite material. The thermal conductivity of the magnetically oriented composite material was significantly improved, as the longitudinally arranged nanowires acted as excellent heat conduction paths, thus improving heat transfer efficiency.

[0070] Table 3 This invention performs breakdown performance tests on Examples 8 and 14-22. The results are as follows: Figure 4 As shown in Table 4, breakdown performance was tested using a BDJC-100kV DC breakdown test. The boost rate was 0.5kV / s. Eight independent measurements were performed on each sample, and the data were statistically analyzed using a two-parameter Weibull distribution.

[0071] Table 4 The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A high thermal conductivity and nonlinear electrical conductivity composite material containing a vertical nanowire array, characterized in that, The invention includes a polymer matrix and modified semiconductor nanowires dispersed within the polymer matrix; the modified semiconductor nanowires are semiconductor nanowires with Fe3O4 nanoparticles loaded on their surface; the modified semiconductor nanowires are arranged in a vertically oriented structure within the polymer matrix with the assistance of a magnetic field. The Fe3O4 nanoparticles account for 1 to 4% of the mass of the modified semiconductor nanowires by mass fraction. The modified semiconductor nanowires comprise 1% to 5% of the polymer matrix by volume fraction. The polymer matrix includes an epoxy resin substrate, a curing agent, and a latent agent; The epoxy resin substrate is any one of bisphenol A type epoxy resin, bisphenol F type epoxy resin, polyphenol type glycidyl ether epoxy resin, aliphatic glycidyl ether epoxy resin, and alicyclic epoxy resin. The curing agent is either methylhexahydrophthalic anhydride or methyltetrahydrophthalic anhydride; The luring agent is any one of neodymium acetylacetonate, 2-methylimidazole and 2-ethyl-4-methylimidazole; The semiconductor nanowires include SiC nanowires; The method for preparing the high thermal conductivity and nonlinear electrical conductivity composite material containing a vertical nanowire array includes the following steps: The modified semiconductor nanowires are mixed with the polymer matrix raw material and then cured in a magnetic field environment to obtain the high thermal conductivity and nonlinear electrical conductivity composite material containing a vertical nanowire array. The curing process employs a gradient curing technique, specifically: maintaining a temperature of 80-100℃ for 1-2 hours, maintaining a temperature of 100-115℃ for 1-2 hours, and maintaining a temperature of 135℃-150℃ for 1-2 hours. The method for preparing the modified semiconductor nanowires includes the following steps: Fe3O4 nanoparticles were loaded onto the surface of the semiconductor nanowires by electrostatic adsorption, and the modified semiconductor nanowires were obtained by separation and drying. The magnetic field strength of the magnetic field environment is 300 Gs.

2. The application of a high thermal conductivity and nonlinear conductivity composite material containing a vertical nanowire array as described in claim 1 as an insulating component, electric field equalization component, or overvoltage suppression component in high-voltage electrical equipment.